SOCIAL INNOVATION PROJECT “EMPOWERMENT AND TRAINING FOR E-COMMERCE FOR SMALL AND MEDIUM ENTERPRISES (SMES) SPECIALIZING IN TRADITIONAL COOKIES FROM KAMPUNG SAWAHAN”: EMPOWERMENT AND TRAINING FOR E-COMMERCE FOR SMALL AND MEDIUM ENTERPRISES (SMES) SPECIALIZING IN TRADITIONAL COOKIES FROM KAMPUNG SAWAHAN - Clarensia Sharlyn Wijaya; Caecillia Hartatdji; Ni Putu Febriana Eka S; Jessica Felicia Soesanto; Kathleen Alexandra (CV. ALIM'SPUBLISHING, 2024)
. This social innovation project is centered on empowering and providing e-commerce training for Small and Medium Enterprises (SMEs) specializing in traditional cookies from Kampung Sawahan. With a focus on the “Kampung Kue Sawahan” in Surabaya, the project aims to address marketing challenges, enhance online presence, and broaden sales channels for local businesses. Key objectives encompass leveraging social media and e-commerce platforms, as well as offering training in product photography. The project's ultimate goal is to benefit the community by resolving marketing issues, expanding business reach, and fostering economic empowerment. The comprehensive implementation involves a two-day program targeting mothers residing in rural areas, local entrepreneurs, and potential resellers. Activities include product photography, content creation, TikTok account setup, and e-commerce training on platforms like Shopee. The anticipated tangible outcomes include an enhancement of online business skills within the